Comparative analysis of flower-meristem-identity gene APETALA2 (AP2) codon in different plant species - Yan-qing WU; Zhi-yuan LI; Da-qiu ZHAO; Jun TAO (Journal of Integrative Agriculture, 2018)
The flower-meristem-identity gene APETALA2 (AP2), one of class-A genes, is involved in the establishment of the floral meristem and the forming of sepals and petals. Codon usage bias (CUB) identifies differences among species, meanwhile dynamic analysis of base composition can identify the molecular mechanisms and evolutionary relationships of a specific gene. In this study, eight coding sequences (CDS) of AP2 gene were selected from different plant species using the GenBank database. Their nucleotide composition (GC content), genetic index, relative synonymous codon usage (RSCU) and relative codon usage bias (RCUB) were calculated with R Software to compare codon bias and base composition dynamics of AP2 gene codon usage patterns in different plant species. The results showed that the usage of AP2 gene codons from different plant species were influened by GC bias, especially GC3s. Overall, base composition analysis indicated that the usage frequency of codon AT in the gene coding sequence was higher than GC among AP2 gene CDS from different plant species. Furthermore, most AP2 gene CDSs ended with AT; AGA, GCU and UGU had relatively high RSCU values as the most dominant codon; the usage characteristic of the AP2 gene codon in Malus domestica was similar to that of Vitis vinifera; Paeonia lactiflora was similar to Paeonia suffruticosa and Solanum lycopersicum was similar to Petunia×hybrida. There was a moderate preference in the usage of AP2 gene codon among different plant species from relatively low frequency of optimal codon (Fop) values and high effective number of codons (ENC) value. This study has revealed the usage characteristics of the AP2 gene codon from the comparision of AP2 gene codon preference and base dynamics in different plant species and provide a platform for further study towards transgenic engineering and codon optimization.